1990
DOI: 10.1007/bf00289227
|View full text |Cite
|
Sign up to set email alerts
|

Does sexist language reflect personal characteristics?

Abstract: We investigated whether or not sexist language in written form can be linked to traditional views of sex roles, assertiveness, psychological androgyny, Christian beliefs, or sexist language in oral form. In Experiment 1, undergraduates were given an essay designed to test written sexist language and several pencil-and-paper personality inventories. No relationship between sexist language and interpersonal assertiveness or psychological androgyny was found. However, those who avoided sexist language were less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
(6 reference statements)
1
13
0
Order By: Relevance
“…These results suggest that the robust effect of gender on attitudes toward sexist language can be explained, at least partially, by a cultural construct, attitudes toward women. This conclusion is similar to those drawn by Jacobson and Insko (1985), Matheson and Kristiansen (1987), McMinn et al (1990), and McMinn et al (1991), who also found connections between aspects of sexist language and attitudes toward women. Taken together, these empirical studies of the link between attitudes toward women and attitudes toward sexist language lend credibility to Whorf's (1940/1956a, 1941/1956b) proposal of a relationship between culture and language.…”
Section: Discussionsupporting
confidence: 89%
“…These results suggest that the robust effect of gender on attitudes toward sexist language can be explained, at least partially, by a cultural construct, attitudes toward women. This conclusion is similar to those drawn by Jacobson and Insko (1985), Matheson and Kristiansen (1987), McMinn et al (1990), and McMinn et al (1991), who also found connections between aspects of sexist language and attitudes toward women. Taken together, these empirical studies of the link between attitudes toward women and attitudes toward sexist language lend credibility to Whorf's (1940/1956a, 1941/1956b) proposal of a relationship between culture and language.…”
Section: Discussionsupporting
confidence: 89%
“…These studies have used forms of BEM Sex Role Inventory (BMSRI; Bem, 1974 ). The studies showed that a masculine gender identity (no matter of biological gender) was associated with more negative attitudes ( Rubin and Greene, 1994 ), while androgynous gender identity has been associated with more positive attitudes, and higher use of gender-fair language ( McMinn et al, 1990 ; Rubin and Greene, 1991 ). Given that Sweden is an egalitarian society, where the distinction between femininity and masculinity is no longer as strongly rooted in traditional feminine and masculine roles, we believe that the strength of gender identity is a better measure than gender roles as measured by BMSRI ( Bem, 1974 ).…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally participants assume the college professor is male. In previous studies (McMinn et al, 1990), scorers of the essay test have achieved an interrater reliability of 1.00. Thus, only one skilled rater was used to score the essay responses in this study.…”
Section: Methodsmentioning
confidence: 93%
“…In their studies of the effects of sexist language, McMinn and his colleagues have used an essay response to open-ended questions to evaluate college students' tendencies to use sexist language McMinn et al, 1990;McMinn, Troyer, Hannum, & Foster, 1991). One such question was, "A business executive discovers a long-time employee has been stealing from the company.…”
mentioning
confidence: 99%